Uji Klinik Khasiat Sediaan Rebusan Ramuan Jamu Hipertensi Dibanding Seduhan Jamu Hipertensi - Agus Triyono; Peristiwan Ridha; Danang Ardianto (Fakultas Farmasi Universitas Pancasila, 2018)
To search for scientific evidence the efficacy of herbal medicine, has conducted clinical trial the efficacy of hypertension herbs compared with hydrochlorotiazide. Efficacy of clinical trials were conducted with the design open-label, randomized clinical trials and parallel design. It was involving 80 subjects who have met the inclusion and exclusion criteria. Subjects randomized study that is divided into two groups, a herbs group and hydrochlorotiazide group. Subjects performed once a week to check the complaint history, the development of clinical symptoms, the possibility of side effects and diagnostic physical examination. Assessment score of quality of life by questionnaires Short Form 36 (SF-36) every four weeks. Results showed that administration of herbal medicine for 56 days hypertension, lower blood pressure (systolic and diastolikic) is equivalent to hydrochlorotiazide (HCT). Lowering blood pressure to normal (normotensive) 62.7% of the subjects. Eliminating the clinical symptoms of hypertension (dizziness / headache, stiff neck / whiny and myalgia) herbs group subjects at almost the same time with the hidrochlorthiazide group. Raising the quality of life scores (SF-36) subjects herbs group equivalent to the increase in quality of life scores (SF-36) hydrochlorotiazide group.